Eutrophication in coastal aquatic systems and the utility of nutrient budgets in their management - Souza, Christina Alzira Rumilda Rita de (2012)
Dissertação de mest., Gestão da Água e da Costa, Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2010